Laboratory studies of the impact of a roller sorting machine on potato tubers - A. S. Dorokhov; A. V. Sibirеv; A. G. Aksenov; N V. Sazonov (Аграрная наука Евро-Северо-Востока)
Existing machines for sorting potatoes damage marketable products as a result of the interaction of potato tubers with each other, with working organs and soil clods. The greatest percentage of damage to potato tubers occurs as a result of their interaction with the working bodies of the machines for sorting. In order to determine the place of the greatest force impact of the working bodies of the sorting machines on the potato tuber and to carry out subsequent measures to eliminate negative effects in the design of these machines, laboratory studies were carried out using the "The TuberLog Electronic Potato" software tool. The article provides the results of comparative studies of the force impact of the sorting surface on the electronic potato tuber at various values of the forward speed of movement and interaction time of the working surface of roller-type machine for sorting potato tubers. Analysis of graphical dependencies showed that the greatest force impact (up to 22 N) on a potato tuber falls on the time interval of values from 8.5 to 9.5 s, while the standard deviation and coefficient of variation are σ = 5.7 and ν = 24.8 %, respectively. The analysis of the experimental data showed that the most "gentle" force impact of the working bodies of the sorting machine at the forward speed of the roller belt of 1.4 m / s throughout the entire technological process of sorting is the minimum force impact on the sorted products in the range from 3 to 6.5 N, which is 28-31% of the maximum force impact of working bodies at speeds of 1.8 and 2.2 m/s.